Alteration of endosomal trafficking is associated with early-onset parkinsonism caused by SYNJ1 mutations - Fasano, Dominga (Cell Death Dis, 2018)
Recently, a new form of autosomal recessive early-onset parkinsonism (PARK20), due to mutations in the gene encoding the phosphoinositide phosphatase, Synaptojanin 1 (Synj1), has been reported. Several genes responsible for hereditary forms of Parkinson’s disease are implicated in distinct steps of the endolysosomal pathway. However, the nature and the degree of endocytic membrane trafficking impairment in early-onset parkinsonism remains elusive. Here, we show that depletion of Synj1 causes drastic alterations of early endosomes, which become enlarged and more numerous, while it does not affect the morphology of late endosomes both in non-neuronal and neuronal cells. Moreover, Synj1 loss impairs the recycling of transferrin, while it does not alter the trafficking of the epidermal growth factor receptor. The ectopic expression of Synj1 restores the functions of early endosomes, and rescues these trafficking defects in depleted cells. Importantly, the same alterations of early endosomal compartments and trafficking defects occur in fibroblasts of PARK20 patients. Our data indicate that Synj1 plays a crucial role in regulating the homeostasis and functions of early endosomal compartments in different cell types, and highlight defective cellular pathways in PARK20. In addition, they strengthen the link between endosomal trafficking and Parkinson’s disease.